Prevention: carotid endarterectomy, angioplasty, and stenting - Hoh, Brian (Henry Stewart Talks, 2020)
Introduction to carotid stenosis, NASCET trial, ACAS trial, ACST trial, CREST trial, CEA: general vs. regional anesthesia, CEA: standard vs. eversion technique, CEA: routine vs. selective shunting, CEA: patch vs. primary closure, CAS: variations in technique, Indications and contraindications for CAS, Carotid dissection, Acute carotid occlusion, Cerebral hyperperfusion syndrome, CREST 2 trial